ANALISIS KESEIMBANGAN LINTASAN PERAKITAN HYDRAULIC EXCAVATOR 135 DENGAN MENGGUNAKAN METODE HEURISTIK UNTUK MENINGKATKAN EFISIENSI DAN PRODUKTIVITAS KERJA - Rahmi Silmie Sudhana (2023)
PT. ABC is one of the companies which produces various heavy equipment products; such as, the Hydraulic Excavator 135. The distribution of workload between work stations on the Hydraulic Excavator 135 assembly line is known to be uneven which leads to the efficiency level to be relatively low; besides, work accumulation and work queues occur. This study is expected to be able to balance the assembly line to be more efficient by implementing a heuristic approach. The heuristic approach in this study used the Helgeson-Birnie method and the Moodie Young method. The results of the two methods are compared with the initial line conditions and it shows that the Moodie Young method has good results of the line balancing performance of the Hydraulic Excavator 135. It is because the Moodie Young method produces a line efficiency level of 78.74% from 23.62% previously, the original balance delay rate is around 76.38% to 21.26%, and the smoothness index value is around 84.91 minutes. In addition, the number of work stations on the line has decreased by around 7 stations, from 10 to 3 effective work stations.